Public advertising plan study for effective shelter at a crisis moment - Lee, Jei-Young; Kim, Jee Hee (Edelweiss Applied Science and Technology, 2025)
This study investigates the subjectivity of emergency rescue students regarding public advertising strategies for effective evacuation during a crisis situation. Design/Methodology/Approach: This study was conducted using an in-depth Q survey, and the data were analyzed. The study identified types through a survey using Q-factor analysis via the PC QUANL program. Findings: The analysis using the QUANL program revealed a total of four types. (1) Type 1 (N=7): Education-training & communication-strategy Type, (2) Type 2 (N=6): Advance preparations Type, (3) Type 3 (N=6): Media information use & active practice Type, (4) Type 4 (N=4): Report & media information use Type. Conclusion: This study will provide specific guidelines for effective evacuation during a crisis. It is essential to establish a standard manual that can respond to urgent disasters. A detailed explanation of various situations in preparation for dangerous times should be included in the basic procedures. Practical implications: Public relations strategies for active improvement concerning 'effective evacuation during a crisis' should be prepared. There should be sufficient promotional strategies and tactics that can be immediately utilized during a disaster.